ROUTLEDGE ECONOMIC HISTORY OF WAR - Eloranta, Jari; Land, Jeremy; Kuorelahti, Elina, 1979-; Fishback, Price Van Meter (Routledge Handbooks in Economic History., 2025)
The Routledge Economic History of War presents a broad overview of the latest research on the longlasting changes and effects that collapsing security in international relations has had on the world's economies and societies.Arranged around five key themes - Fiscal and Military Capacity, Military Spending, Economic Effects of War, War and Institutions, and Business and War - this handbook features contributions from an international range of scholars, on varying methodological approaches, theories, and geographical arenas. Encompassing a range of disciplinary approaches, the main focus is on how economic history can provide insights into the societal impact of war, addressing issues such as how war preparations and arms races affect government spending, the direct economic effects of war, and how societies adjust to the economic realities of rearmament and recovery. This volume also explores whether wars change or alter institutions such as governments, religion, and democracy. It also looks at what lessons we can learn from the past about military spending, state capacity, and the effects of war on both individual societies and global cooperation.Ultimately, this book provides a broad overview of the methodological, geographical, and multidisciplinary range of the economic history of war and demonstrates how war, economics, institutions, and society are inextricably linked throughout history.